TEACHING JOB INTERVIEW PROGRAM AT LTE CRUISE PARE KEDIRI - Alfinani, Ahmad Alfan (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
Job interview is important to know the characteristic of employees’ candidates. Due to this reason, LTE Cruise Ship offered a program about job interviews for cruise ships. This program was collaborated with a cruise ship agency, so, the students could be hired easily after graduation. This study aims to carry out the preparation of teaching of job interview program at LTE Cruise Pare Kediri, the teaching-learning process, the students’ response, and the evaluation. This study used a qualitative method. There are some instruments used to collect the data, they are; observation checklist, interview guide, and list of documents. This research reveals some findings related to the focus, they are; (1) the preparation of teaching job interview program at LTE Cruise was supported by syllabus and lesson plan based on the cruise ship agency, (2) the teaching-learning process consisted of 8 meetings for material and simulation, (3) the students give good respond because they feel help with the material to prepare their job interview in a cruise ship, and (4) the evaluation was done twice in the middle and final. Through this result, it was suggested that the manager could make the complete syllabus, the tutor could give warm-up before the material, the students suggest to do individual practice in arranging sentences, the readers to look for another course that over the material of job interview for cruise ship, and for the next researcher was suggested to look for unique courses about cruise ship in different English course.